Interconexión entre las funciones de onda en representaciones de coordenadas, impulsos y estados coherentes - D. Campos (Momento, 1996)
We find a natural expansion for coherent-state representation of a quantum-mechanical state, in which position-space wave function and its derivatives appear as the unknown coefficients of the expansiono by application of a suitable rule, it is possible to deduce similar results for momentum-space wave function and its deri vati ves.